Dampak Covid-19 Terhadap Pendapatan Lembaga Keuangan Syariah (Studi Kasus Pada BPRS Adam Kota Bengkulu) - Abdul Kadir; Lindra Zanjaya; Panca Desriansyah Herlangga; Asnaini Asnaini; Yunida Een Fryanti (Journal of Economic, Bussines and Accounting (COSTING), 2022)
COVID-19 was first discovered in Wuhan, China at the end of December 2019. This virus spread very quickly and has spread to almost all countries, including Indonesia. In just a few months, COVID-19 also had a fairly broad impact on community activities, one of which was the economic impact on banking financial institutions, both conventional and Islamic banks. In this scientific paper, the author describes how the impact caused by COVID-19, how the income growth of Islamic financial institutions at BPRS Adam in the midst of the COVID-19 pandemic and the strategies implemented to overcome the impact of the COVID-19 pandemic. This research uses descriptive qualitative research method. This is due to the freedom to obtain information from the latest news from trusted sources, regarding the impact of COVID-19, the author also obtained several news samples from the internet and then combined them into a result. BPRS assets have decreased compared to the same time before the COVID-19, as seen from the income in 2018 of Rp. 895,076, in 2019 decreased 22.5% or Rp. 390,932 and in 2020 BPRS Adam's income increased by 84.2% or Rp.2,688,888 which was because BPRS Adam had implemented a digital banking strategy Keywords:Impact of COVID-19, BPRS income, government policy